Employing Running Dictation for Developing Students’ Vocabulary Mastery for the Tenth-Grade Students of SMAN 1 Nita - Sesilia Selvina; Marselus Yumelking; Genoveva Dua Eni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Click here and insert abstract your text. Insert an abstract of 200-300 words, giving a brief account of the most relevant aspects of the paper. The study purpose was The study purpose was to improve students’ vocabulary mastery, particularly in writing skills, through the implementation of the Running Dictation technique. Vocabulary is a fundamental component in English language learning because it enables students to construct sentences, express ideas, and convey meaning effectively in written communication. However, based on preliminary observations at SMAN 1 Nita, many tenth-grade students experienced difficulties in vocabulary mastery, low motivation to write, lack of confidence, and limited participation in English learning activities. These problems resulted in poor writing performance and minimal engagement during classroom activities. Therefore, an active and cooperative learning strategy was needed to enhance students’ vocabulary development and writing ability. Materials and methods. This study employed a Classroom Action Research (CAR) design consisting of three cycles, each involving planning, action, observation, and reflection stages. The participants were 18 tenth-grade students of Class X-C selected through purposive sampling. Data were collected using vocabulary writing tests (pre-test and post-test), observation sheets, interviews, and field notes. Qualitative data were used to describe students’ learning behavior, motivation, and classroom interaction, while quantitative data were analyzed to measure improvements in vocabulary mastery after the implementation of the Running Dictation technique. Results. The findings indicated a significant improvement in students’ vocabulary mastery across the cycles. The mean score increased from 62.35 in Cycle I with 22.22% mastery, to 77.26 in Cycle II with 77.78% mastery, and reached 87.44 in Cycle III with 100% mastery. Students also showed higher motivation, better cooperation, and greater confidence in writing. Conclusions. The study concludes that the Running Dictation technique is effective in improving students’ vocabulary mastery and writing skills by creating an active, enjoyable, and meaningful learning environment.